Brain AQP4 during experimental acute liver failure - Shuliatnikova, T. V.; Tumanskyi, V. O.; Шулятнікова, Тетяна Володимирівна; Туманський, Валерій Олексійович (My University, 2022)
Hepatic encephalopathy (HE) was defined as a complex neuropsychiatric syndrome triggered by severe liver pathology and manifesting by covert and overt alterations up to hepatic coma and death [1]. Acute liver failure (ALF) results in acute hepatic encephalopathy (AHE) characterized by brain edema caused by complex mechanisms closely linked to ammonia toxicity [2]. Astrocytes are central brain cells the most sensitive to ammonia as being primarily source of glutamine synthetase (GS), therefore astrocyte swelling is a principal feature of AHE brain [1-3]. Aquaporin- 4 (AQP4) is one of the central astrocyte molecules responsible for water homeostasis and cell volume in health and disease and presents the most abundant water channel in the CNS. According to current HE pathophysiology, alteration of AQP4 regulation can play a central role in the brain edema progression [1]. Considering high heterogeneity of astroglia populations in the CNS, AQP4 involvement to the links of HE can also sustain mentioned conventional diversity. The purpose of the study was determining
Shulyatnikova T. V. - https://orcid.org/0000-0002-0196-9935; Tumanskiy V. O. - https://orcid.org/0000-0001-8267-2350.